Pelatihan Perawatan Payudara Menuju Sukses ASI Eksklusif di Sidoarjo - Hastuti, Puji; Budiarti, Astrida; Ernawati, Dwi; Saidah, Qori’ Ila; Fatimawati, Iis; Faridah, Faridah (Institut Riset dan Publikasi Indonesia (IRPI), 2025)
Breast milk is the perfect food for babies. Breast milk contains essential and complete nutrients that babies need for their growth and development. However, in reality, there are still many mothers who do not provide exclusive breastfeeding due to various factors, one of which is breast milk that is not smooth. Breast care is an effort to launch breast milk production, so that it meets the needs of the baby. The purpose of this activity is to conduct community service by providing breast care training towards exclusive breastfeeding success for breastfeeding mothers in Kalanganyar Village, Sedati, Sidoarjo. Activities include pretest, training, discussion and question and answer, and posttest to evaluate the level of understanding of breastfeeding mothers. After the training, 90% of pregnant women had good knowledge